SISTEMATIZAÇÃO DA ASSISTÊNCIA DE ENFERMAGEM PARA CRIANÇAS DA PRIMEIRA INFÂNCIA ATENDIDAS EM UNIDADE ESTRATÉGIA SAÚDE DA FAMÍLIA - Lederhans, Ana Carolins Feldns (2019)
Introduction: Early childhood care is a prime social investment. It is at this stage that the base and the sustentation of its future achievements are developed. In view of this, the nurse must provide integral and resolutive assistance, using the Systematization of Nursing Assistance (SAE). General objective: To implement SAE in a Family Health Strategy Unit (ESF), focusing on Nursing diagnoses and interventions for infants, based on the International Classification of Nursing Practice (CIPE®). Specific objectives: To identify the nursing diagnoses and interventions prevalent in early childhood children attending a FHS; To elaborate a plan of interventions of Nursing, based on the diagnoses prevalent in children of the first childhood, attended in the FHT; and implement Nursing interventions based on the CIPE® catalog. Methodology: This is a study of the type Convergent Care Research, which was developed in an ESF of a small municipality, in the central-western region of the state of Rio Grande do Sul, Brazil, in the period between May to October 2018. Data collection took place during Nursing consultations in the follow-up of children in early childhood. Results: Two articles emerged from the data. In the first article, entitled: "Nursing Diagnoses and Interventions in an ESF Unit for Early Childhood Children", the objective was to identify Nursing diagnoses and interventions for use during the Nursing Process (PE) in a FHS. A total of 49 diagnoses and 189 nursing interventions were built, focusing on children and families. And, in the second article, entitled "Process of Implantation of the Systematization of Nursing Assistance in a Family Health Strategy Unit: Potentialities and Barriers", the objective was to describe the process of implantation of SAE in a FHS. Final considerations: The construction of Nursing diagnoses and interventions facilitated the implantation of PE and SAE in the FHT, thus reducing the tendency of the fragmentation of the stages of the PE, providing integral care to the child, better resolution of the problems presented, the promotion of humanization and empathy on the part of Nursing professionals. Product and its applicability: The set of Nursing diagnoses and interventions for early childhood children to be used in the FHS, using CIPE® version 2017, in order to qualify health care in the PE results in the following social benefits and impacts: Methodological improvement, standardization and agility of PE; More effective interaction between professional-user; Planned assistance, offering security to the user and his family; Quality and resolution in service; Professional visibility and increase the quality of life of the population.